Design improvement of wira's driver seat usine integrated DFA and VE - Mgt Arnaz, Mgt Ramli (2007)
Wira driver's seat is a complicated product that consist hundred of part and the material representative are from steel to rubber. Some of the part is easy to assemble and some of it is difficult to assemble. Parts that are difficult to assemble could cause a rise of cost in terms of labor and time. The objectives of this project are to improve the design of Proton Wira driver's seat by using integrated Value Engineering (YE) and Design for Assembly (DFA) and to make the comparative analysis between current design and proposed design in terms of assembly effectiveness. The flow of this project is started from collecting Wira seat information and using YE approach to identify the function identification and implement function analysis. Then, the alternative design will be generated and the best alternative design will be evaluated using Pugh method. After that, the proposed design will be compared with current design of Wira seat using DFA approached. The result shows that the DFA Index for the proposed design of Wira driver's seat is higher than current design that is 4.7 compare to 4.4. Hence, it can be concluded that the integrated of VE and DFA method can improve the design of Wira driver's seat in terms of assembly effectiveness.